Long-term oyster shell powder applications increase crop yields and control soil acidity and cadmium in red soil drylands - Hao Li; Yan Wu; Jiwen Li; Tianfu Han; Kailou Liu; Shangshu Huang (Frontiers in Plant Science)
The intensification of agricultural production has significantly reduced land availability, necessitating continuous cropping cycles that degrade soil quality and inhibit crop growth. While the short-term use of soil amendments has shown significant potential for mitigating these challenges, few studies have explored their long-term effects on acidified soils and heavy metal accumulation. Between 2013 and 2018, a field experiment was conducted in the peanut (Arachis hypogaea L)-growing region of Jinxian County, Jiangxi Province, to investigate the long-term effects of oyster shell powder applied to upland red soil. Before the experiment, the soil properties were as follows: pH, 4.54, total soil cadmium (Cd) content, 0.49 mg kg-¹; and available Cd content, 0.25 mg kg-¹. The experiment included three treatments combining chemical fertilizers with oyster shell powder at application rates of 750, 1500, and 2250 kg ha-¹ (L750, L1500, L2250) and a control with only chemical fertilizer (L0). From 2013 to 2018, peanut yield among all treatments was assessed at maturity. Soil pH was then measured using a pH meter with a 2.5:1 water-to-soil ratio. Exchangeable hydrogen and aluminum were determined using the potassium chloride exchange-neutralization titration method. Meanwhile, available Cd content was extracted using 0.1 M CaCl2 and measured with a flame atomic absorption spectrophotometer. While all treatments showed an annual decline in peanut yield from 2013 to 2018, but oyster shell applications significantly reduced the rate of crop yield decline. Compared to L0, the yields of L750, L1500, and L2250 treatments increased by 5.55%-19.42%, 8.64%-28.74%, and 15.43%-37.01%, respectively. Soil pH values in the L750, L1500, and L2250 treatments were higher than the L0 treatment by 0.03-0.31, 0.16-0.48, and 0.28-0.65 units, respectively. Their exchangeable hydrogen contents decreased by 10.17%-24.24%, 16.67%-27.94%, and 23.40%-29.44%. In addition, exchangeable aluminum contents decreased by 5.05%-26.09%, 23.23%-46.27%, and 39.73%-66.97%. In contrast, soil available Cd contents in the L750, L1500, and L2250 treatments were lower than the L0 treatment by 7.96%-19.29%, 9.56%-30.71%, and 13.94%-34.65%, respectively. Correlation analysis revealed that soil pH was positively associated with peanut yield and negatively correlated with exchangeable hydrogen, exchangeable aluminum, and available Cd. For every 0.1 unit increase in soil pH, peanut yields increased by 119.62-389.82 kg ha-¹, while available Cd decreased by 0.06-0.12 mg kg-¹. Therefore, these findings demonstrate the efficacy of continuous oyster shell powder application in controlling soil acidification and reducing Cd levels in upland red soil.